2010
DOI: 10.1007/s10336-010-0508-x
|View full text |Cite
|
Sign up to set email alerts
|

Egg survival is related to the colour matching of eggs to nest background in Black-tailed Gulls

Abstract: A long-standing hypothesis posits that, for species with exposed nests, a close match between the colour of the eggs and that of the nest in which they are laid should enhance egg survival, but this has rarely been tested in a rigorous manner. Here, we demonstrate the effects of egg-nest colour matching on egg survival in Black-tailed Gulls (Larus crassirostris) on Hongdo Island, Korea. We quantified the ground colour of eggshells and that of the nest background using a digital camera and computerized RGB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…This is similar to the previous study on Japanese quail, which has been shown to seek out a substrate that best matches their egg coloration as a nest position to provide the most effective camouflage (Lovell et al, 2013). Furthermore, avian egg survival ratio is related to the color matching of eggs to nest background, as in eggs of Black-tailed Gulls (Larus crassirostris) (Lee et al, 2010). The population density (21.5/km) of four-eyed turtles was the highest in midstream of the stream (Xiao, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This is similar to the previous study on Japanese quail, which has been shown to seek out a substrate that best matches their egg coloration as a nest position to provide the most effective camouflage (Lovell et al, 2013). Furthermore, avian egg survival ratio is related to the color matching of eggs to nest background, as in eggs of Black-tailed Gulls (Larus crassirostris) (Lee et al, 2010). The population density (21.5/km) of four-eyed turtles was the highest in midstream of the stream (Xiao, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…For instance, Japanese quail (Coturnix japonica) females choose a substrate that best matches their egg background coloration in order to provide the most effective camouflage (Lovell et al, 2013). In recent years, some studies have suggested that background matching is associated with reduced risk of predator detection (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, during these periods in which the eggs may be uncovered to alleviate overheating, unattended nests may be easier to locate by predators (Keller, 1989;Opermanis, 2004;Prokop & Trnka, 2011), because the eggs are less well camouflaged. As shorebirds suffer high nest predation rates (e.g., Fraga & Amat, 1996;Neuman et al, 2004;Saalfeld et al, 2011), better egg camouflage may be adaptive because this may improve nesting success (Solís & de Lope, 1995;Lee et al, 2010;Colwell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%